Depression Over Psoriasis: Assessment of associated Relief by addition of ADalimumab for the treatment of Psoriasis: Observational study (DORADO - Ps) - Ayman Elgendi; Hanan Nada; Al Sadat Mosbeh; Mona Maatouk; Majdy Abulghany; Wayne Gulliver (Wolters Kluwer Medknow Publications, 2015)
Background: Psoriasis is associated with a variety of psychological difficulties, including poor self-esteem, sexual dysfunction, anxiety, depression, and suicidal ideation. Objectives: The aim of this study was to obtain further data on the extent of depression among psoriatic patients, the effectiveness of adalimumab treatment on the depression symptoms associated with psoriasis and to explore the association between improvement in depression symptoms and improvement in Psoriasis Area and Severity Index. Methods: The effects of adalimumab (40 mg every other week) on ZDS score and PASI at week 24 were assessed. Relationships between ZDS and PASI were assessed. Changes in ZDS score were compared for patients with and without a 75% or greater reduction in baseline PASI score. An improvement of 6 points or more in the Zung depression scale was considered a clinically meaningful improvement. Results: Forty five Patients with moderate to severe psoriasis were assessed for depression symptoms at baseline and week 24 using the Zung Self-rating Depression Scale (ZDS). At month 6 after starting adalimumab, 80% of enrolled patients achieved 75% improvement in their PASI score (PASI75) at month 6 of adalimumab therapy and 97.8% achieved a meaningful improvement of Zung depression score (more than 6 points decline in the Zung depression score). Age at time of assessment significantly predicted depression (p = 0∗030), with the younger age predicting a higher depression score (standard co-efficient -.451). Achieving PASI 75 could significantly predict improvement in depression (p = 0.002, standard coefficient-.746). Conclusion: Adalimumab may be associated with relief symptoms of depression in patients with moderate to severe psoriasis. Reductions in depression symptoms were significantly correlated with reductions in psoriasis severity.